Changes : English for international communication : INTRO workbook - Richards, Jack C.; Hull, Jonathan; Proctor, Susan (Cambridge : Cambridge University Press, 1998)
Hello. My name is Maria. What's this in English? Where are you from? Where is the sports club? I love strawberries...
Keywords: English language; Foreign speakers; English language -- Textbooks for foreign speakers; English language -- Study and teaching -- Foreign speakers; Communication, International